Sarcocystosis in Farm Animals in Brazil: A One-Health Approach - dos Santos Pinto, Michel [UNESP]; Neto, João Alfredo Biagi Camargo [UNESP]; Lopes, Carlos Wilson Gomes; Paiva, Fernando; de Barros, Luiz Daniel; Felippelli, Gustavo [UNESP]; de Souza Rodrigues, Fernando; Widmer, Giovanni; Bresciani, Katia Denise Saraiva [UNESP] (MDPI, 2025)
Sarcocystosis is a parasitic infection caused by obligate intracellular coccidia, which infect humans, domestic animals, and wildlife. More than 200 Sarcocystis species have already been identified, but for many of these, the life cycle, pathogenesis, and clinical signs remain unclear. The infection is cosmopolitan, with high prevalence in cattle herds worldwide. Although the clinical disease in definitive hosts is considered rare, the high number of sporocysts released by them drives the incidence in production animals. Furthermore, sarcocystosis has some One Health relevance due to its zoonotic potential, especially concerning species infecting primates. Few studies have reported on the epidemiology of sarcocystosis in Brazil. However, a high prevalence of the disease was found in areas where investigations of Sarcocystis species were conducted, which highlights the potential for foodborne transmission to humans. Therefore, it is relevant to study this parasitic disease so that control and prophylaxis measures can be adopted. This study aims to review the current state of knowledge on Sarcocystis spp. in farm animals in Brazil.